Pengaruh Manajemen Talenta Dan Pengembangan Karier Terhadap Kinerja Karyawan Di Lembaga Amil Zakat Nasional Baitul Maal Hidayatullah Jakarta - Muhammad Nofal Defano; Dewi Kurniawati; Roy Prakoso (Jurnal Riset Bisnis, 2025)
This study aims to determine the effect of talent management and Career Development on employee performance in working at Laznas BMH. The type of data used in this study is quantitative data. The sampling technique used is random sampling consisting of 70 amil respondents at Laznas BMH. The analysis techniques used are Validity and Reliability Test, Classical Assumption Test, Regression Analysis, Determination Coefficient and Hypothesis Test using SPSS 25. This study examines the dimensions of talent management consisting of Sourcing, Aligning, Retain, Learn & Develop, and Reward. This research also examines the Career Development dimension which consists of Fair treatment in career, Concern of direct supervisors, Information about promotion opportunities, Interest in being promoted, and Level of satisfaction. In addition, this study also examines the employee performance dimension which consists of work quality, work quantity, cooperation, responsibility, and initiative. The results showed that talent management has a positive and significant effect on employee performance at Laznas BMH, Career Development has a positive and significant effect on employee performance at Laznas BMH, Talent management and Career Development have a positive and significant effect on employee performance at Laznas BMH. The findings of this study can assist Laznas BMH in developing amil staff who possess both technical skills and a broad understanding of contemporary zakat management.